Dielectric investigation on some binary mixtures of hockey-stick-shaped liquid crystal and octyloxy-cyanobiphenyl. (2nd September 2019) - Chakraborty, Susanta; Chakraborty, Anish; Das, Malay Kumar; Weissflog, Wolfgang
ABSTRACT: We report the measurement of temperature-dependent dielectric parameters in some binary liquid crystal mixtures comprising of a hockey-stick-shaped mesogen 4-(3-decyloxyphenyliminomethyl) phenyl-4-decyloxycinnamate (SF7) and calamitic compound 4′-octyloxy-4-cyanobiphenyl (8OCB). All the investigated mixtures possess a large positive dielectric anisotropy (Δ ε ), although a noticeable reduction has been found by increasing the diverse-shaped dopant concentration. Investigation on the pretransitional behavior in the vicinity of isotropic to nematic ( I – N ) phase transition suggesting a tricritical character for all the studied mixtures. Parameterization of dielectric permittivity close to the nematic to smectic- A ( N –Sm- A ) phase transition exhibits non-universal values of the critical exponents describing a second-order nature of the transition. Systematic variation of critical exponents against dopant concentration and McMillan ratio reveals a well consistency with those obtained from the high-resolution optical birefringence measurements.